Participatory scenario planning to facilitate human–wildlife coexistence. Issue 6 (31st May 2021) - Jiren, Tolera Senbeto; Riechers, Maraja; Kansky, Ruth; Fischer, Joern
Abstract: Fostering human–wildlife coexistence requires transdisciplinary approaches that integrate multiple sectors, account for complexity and uncertainty, and ensure stakeholder participation. One such approach is participatory scenario planning, but to date, this approach has not been used in human–wildlife contexts. We devised a template for how participatory scenario planning can be applied to identify potential avenues for improving human–wildlife coexistence. We drew on 3 conceptual building blocks, namely the SEEDS framework, the notion of critical uncertainties, and the three‐horizons technique. To illustrate the application of the proposed template, we conducted a case study in the Zambezi region of Namibia. We held 5 multistakeholder workshops that involved local people as well as numerous nongovernment and government stakeholders. We identified 14 important wildlife species that generated multiple services and disservices. The subsequent benefits and burdens, in turn, were inequitably distributed among stakeholders. Government actors played particularly influential roles in shaping social‐ecological outcomes. We identified 2 critical uncertainties for the future: the nature of governance (fragmented vs. collaborative) and the type of wildlife economy (hunting vs. photography based). Considering these uncertainties resulted in 4 plausible scenarios describing future human–wildlife coexistence. Stakeholders did not agree on a single preferred scenario, but nevertheless agreed on several high‐priority strategies. Bridging the remaining gaps among actors will require ongoing deliberation among stakeholders. Navigating the complex challenges posed by living with wildlife requires moving beyond disciplinary approaches. To that end, our template could prove useful in many landscapes around the world. Abstract : Article impact statement : Participatory scenario planning holds great promise to open new avenues for human–wildlife coexistence in landscapes around the world. Abstract : Planeación de Escenarios Participativos para Facilitar la Coexistencia Humano‐Fauna Resumen: El fomento a la coexistencia humano‐fauna requiere de estrategias transdisciplinarias que integren a múltiples sectores, consideren la complejidad y la incertidumbre y aseguren la participación de los actores. Una de estas estrategias es la planeación de escenarios de participación, pero hasta la fecha no se ha usado dentro de contextos humano‐fauna. Diseñamos un modelo para poder aplicar la planeación de escenarios participativos para identificar vías potenciales para mejorar la coexistencia humano‐fauna. Nos basamos en tres componentes conceptuales básicos, principalmente el marco de trabajo SEEDS, la noción de incertidumbres críticas y la técnica de los tres horizontes. Para ejemplificar la aplicación del modelo propuesto, realizamos un estudio de caso en la región del Zambeze en Namibia. Realizamos cinco talleres con múltiples actores, los cuales involucraron a los habitantes locales y a numerosos actores gubernamentales y no gubernamentales. Identificamos 14 especies de fauna importantes que generan múltiples servicios y perjuicios. Los beneficios y problemas subsecuentes, en cambio, estaban distribuidos injustamente entre los actores. Los actores gubernamentales tuvieron notablemente un papel de mucha influencia en la formación de los resultados socioecológicos. Identificamos dos incertidumbres importantes para el futuro: la naturaleza de la gestión (fragmentada versus colaborativa) y el tipo de economía faunística (basada en la cacería versus basada en la fotografía). Cuando consideramos estas incertidumbres, obtuvimos como resultado cuatro escenarios posibles descriptivos de la coexistencia humano‐fauna en el futuro. Los actores no estuvieron de acuerdo sobre ningún escenario preferido; sin embargo, sí coincidieron en varias estrategias de prioridad alta. El cierre de las brechas restantes requerirá de una continua deliberación entre los actores. La navegación de los retos complejos generados por la convivencia con la fauna requiere ir más allá de las estrategias disciplinarias. Para este fin, nuestro modelo podría ser útil en muchos paisajes alrededor del mundo.